The Effect Of Prenatal Exercise On Back Pain Among Third-Trimester Pregnant Women In The Working Area Of Teras Terunjam Health Center, Mukomuko Regency, Bengkulu Province In 2025 - Sunarsih Sunarsih; Febra Ayudia; Ronalen Br Situmorang (Universitas Dehasen Bengkulu, 2026)
Back pain is one of the most common complaints experienced by pregnant women in their third trimester due to physiological changes, posture, and weight gain during pregnancy. One non-pharmacological measure that can be taken to reduce back pain is prenatal exercise. This study aims to determine the effect of prenatal exercise on back pain among third trimester pregnant women in the Working Area of Teras Terunjam Health Center. This study used a quantitative method with a quasi-experimental design using a one-group pretest and posttest design. The population in this study consisted of all pregnant women in their third trimester with a gestational age of 28–30 weeks in the working area of Teras Terunjam Health Center, with a sample size of 32 respondents selected using total sampling technique. The research instrument used was the Numeric Rating Scale (NRS) to measure the level of back pain before and after performing pregnancy exercises. Pregnancy exercises were performed twice a week for two weeks. Data analysis was performed using the Paired Sample T-Test because the data was normally distributed with a significance level of α = 0.05. Based on the results of the study, before the pregnancy exercises were carried out, half of the pregnant respondents experienced moderate back pain, namely 16 people (50%). After the pregnancy exercises were carried out, most of the respondents experienced mild back pain, namely 22 people (68.8%). The statistical test results showed a p-value of 0.000 (p < 0.05), which means that there is a significant effect of pregnancy exercises on reducing back pain in third trimester pregnant women. The conclusion of this study is that pregnancy exercises have a significant effect on reducing back pain in third trimester pregnant women. Health workers are advised to increase education and implementation of prenatal exercises on a regular basis as an effort to improve the comfort and health of pregnant women.